Reception of Cybernetics in Colon Classification - Gopinath, M. A. (Journal of Information and Knowledge, 1989)
As a preliminary measure, a rapid survey is given of the difficulties experienced in arriving at the final class numbers for Biochemistry, Statistical Calculus, and Geopolitics. Then, a more detailed account is given of the successive positions given to cybernetics’ in CC. If first looked like a two-phased subject. Then, it was made successively a canonical Basic Subject of Mathematics, a Distilled Main Subject, and finally as a new Main Subject with its position between Mathematics and Physics. The class numbers to be given to branches of applied cybernetics are also discussed. Then a similar account is given of the successive positions given to this new subject in DC.